Electrical stimulation for the treatment of urinary incontinence in women - Gałczyński, Krzysztof; Romanek, Katarzyna; Kulik-Rechberger, Beata; Rechberger, Tomasz (Menopause Review/Przegląd Menopauzalny, 2011)
Objectives: To describe the rationale for the use of electrical stimulation for the treatment of urinary incontinence and sum up the results of clinical studies assessing these techniques. Design : Review of literature about electrical stimulation and treatment of urinary incontinence. Materials and methods: Medline database was systematically searched to identify abstracts or papers published until 2011. Results: Electrical stimulation has effectiveness of up to 90% in the treatment of stress urinary incontinence, urge urinary incontinence and mixed type of urinary incontinence. Electrodes, placed in the vagina or in the anus, stimulate pelvic floor muscles with current frequency of 20-100 Hz and amperage of about 20 mA. This produces a series of changes in the stimulated area and leads to curing or improvement. Conclusions : Electrostimulation is an effective and safe technique in treating urinary incontinence. In combination with other non-invasive methods it can be useful for a specific group of patients as a first-line treatment or additional treatment before and/or after surgery.